2018
DOI: 10.1523/jneurosci.0015-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral, 3D Arm Movement Kinematics Are Encoded in Ipsilateral Human Cortex

Abstract: There is increasing evidence that the hemisphere ipsilateral to a moving limb plays a role in planning and executing movements. However, the exact relationship between cortical activity and ipsilateral limb movements is uncertain. We sought to determine whether 3D arm movement kinematics (speed, velocity, and position) could be decoded from cortical signals recorded from the hemisphere ipsilateral to the moving limb. By having invasively monitored patients perform unilateral reaches with each arm, we also comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 45 publications
(69 reference statements)
13
58
0
Order By: Relevance
“…Since the activity in the ipsilateral hemisphere during movement of the ipsilateral hand overlapped with the activity during bimanual movement, they argued the overlapping activity was presumably due to the preparation and execution of the movement itself. This evidence fits well with previous decoding studies showing the ability to decode 3D movements purely from activity in the ipsilateral hemisphere 10,11 and that these ipsilateral representations seem to be related to active movement rather than sensory processes (as is likely the case here as well since analyses were restricted to the time leading up to EMG onset) 54 .…”
Section: Potential Role Of the Ipsilateral Hemispheresupporting
confidence: 91%
See 1 more Smart Citation
“…Since the activity in the ipsilateral hemisphere during movement of the ipsilateral hand overlapped with the activity during bimanual movement, they argued the overlapping activity was presumably due to the preparation and execution of the movement itself. This evidence fits well with previous decoding studies showing the ability to decode 3D movements purely from activity in the ipsilateral hemisphere 10,11 and that these ipsilateral representations seem to be related to active movement rather than sensory processes (as is likely the case here as well since analyses were restricted to the time leading up to EMG onset) 54 .…”
Section: Potential Role Of the Ipsilateral Hemispheresupporting
confidence: 91%
“…Although most single-joint unimanual movements are typically associated with activity in contralateral sensorimotor cortices during movement preparation and execution, the ipsilateral sensorimotor cortices seem to play a functional role as well. For instance, it is possible to decode 3D movement kinematics solely from the ipsilateral hemisphere in both monkeys 9 and humans 10,11 , suggesting a robust role for ipsilateral sensorimotor cortices in movement preparation /execution. Meanwhile, lesioning ipsilateral M1 in monkeys leads to a brief behavioral deficit in the ipsilesional hand due to deficits in postural hand control 12 .…”
Section: Introductionmentioning
confidence: 99%
“…We then sought to probe the structure of the neural tuning we observed. We were guided by prior single unit recordings in macaques (Cisek, Crammond, and Kalaska 2003; Rokni et al 2003) and fMRI and ECoG studies in people (Diedrichsen, Wiestler, and Krakauer 2013; Jin et al 2016; Bundy et al 2018) which found that ipsilateral and contralateral movements had correlated representations in motor cortex. If this is the case, we hypothesized that there should also exist laterality-related neural dimensions which code for the side of the body independently of the movement details.…”
Section: Resultsmentioning
confidence: 99%
“…In one participant currently enrolled in the trial, we had a unique opportunity to probe further to characterize how movements of all four limbs are neurally represented in one area of human motor cortex. Previous fMRI and ECoG studies on human precentral gyrus have found that it contains a correlated representation of ipsilateral and contralateral arm/hand movements (that is, matching movements of the ipsilateral and contralateral arms have similar neural representations) (Diedrichsen, Wiestler, and Krakauer 2013; Wiestler, Waters-Metenier, and Diedrichsen 2014; Jin et al 2016; Fujiwara et al 2017; Bundy et al 2018). Macaque studies also show a correlated representation of ipsilateral and contralateral reaching movements (Cisek, Crammond, and Kalaska 2003) that changes during bimanual movements (Rokni et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…18 Lastly, in one of the earliest experiments using functional MRI, Kim and colleagues (1993) showed that the task-evoked activation of the left hemisphere was substantially greater for ipsilateral movements compared to the right hemisphere. 41 In later years, a number of neuroimaging 42,43 and neurophysiologic [44][45][46] studies have provided confirmatory evidence for the role of the dominant hemisphere in organizing bilateral motor outputs. Our results of co-varying deficits between the contralesional and ipsilesional hand in LHD provides further empirical support for the role of the left hemisphere (in our pre-morbidly right-handed group) in the control of both hands.…”
Section: The Role Of the Left Hemisphere In The Bilateral Control Of mentioning
confidence: 97%